A bill to secure more effectually the right of appeal in certain cases (Senate doc. (North Carolina. General Assembly. Senate), 1848)
1848 North Carolina Senate Bill to secure more effectually the right of appeal in certain cases before the justice of peace or in any state courts, with some provisions.